Microsurgical Techniques for the Treatment of Breast Cancer—related Lymphedema: a Systematic Review - Penha, Tiara R. Lopez; IJsbrandy, Charlotte; Hendrix, Nicole A. M.; Heuts, Esther M.; Voogd, Adri C.; von Meyenfeldt, Maarten F.; van der Hulst, Rene R. W. J. (Journal of Reconstructive Microsurgery, 2013)
Background Upper limb lymphedema is one of the most underestimated and debilitating complications of breast cancer treatment. The aim of this review is to summarize the recent literature for evidence of the effectiveness of lymphatic microsurgery for the treatment of breast cancer–related lymphedema (BCRL).Methods A search was conducted for articles published from January 2000 until January 2012. Only studies on secondary lymphedema after breast cancer treatment and those examining the effectiveness of microsurgery were included.Results No randomized clinical trials or comparative studies were available. Ten case-series met inclusion criteria: (composite) tissue transfer (n = 4), lymphatic vessel transfer (n = 2), and derivative microlymphatic surgery (n = 4). Limb volume/circumference reduction varied from 2 to 50% over a follow-up time ranging from 1 to 132 months. Postoperative discontinuation rates of conservative therapy were only reported after composite tissue transfer, ranging from 33 to 100% after 3 to 24 months. Clear selection criteria for lymphatic surgery and lymphatic flow assessment were absent in most studies.Conclusion We identified important methodological shortcomings of the available literature. Evidence acquired through comparative studies with uniform patient selection is lacking. Consistent positive findings with regards to limb volume reduction and limited complications are reasons to further explore these techniques in methodologically superior studies.
Keywords: lymphedema; breast cancer; lymphatic microsurgery